Models Of Sustainable Quality To Improve Implementation Of Quality System Of Qualified Enterprise - Fitria -; Yulmaini -; Elida Purba; Murhadi - (Proceeding International Conference on Information Technology and Business, 2017)
The implementation of quality assurance is based on documents, namely academic documents and quality documents. Academic documents as a plan or standard. The academic document contains the direction/policy, vision-mission, educational standards, research, and community service, as well as academic rules. In contrast to academic documents, quality documents as instruments to achieve and meet established standards. The quality documents consist of quality manuals, procedure manuals, work instructions, supporting documents, and forms. [6] University Quality Assurance It is a Stakeholder concept where university quality assurance system is performed on the basis of internal quality assurance, external quality assurance and program implementation permit. Internal quality assurance is quality assurance conducted by university institution in the way that defined by implementing university. The parameters and methods of measuring the results are determined by the college according to its vision and mission. By carrying out internal quality assurance, the higher education institution should conduct an internal evaluation called periodical self-evaluation. Self-evaluation is intended to seek Guidance of Quality Assurance System of Higher Education with continuous quality improvement. Keywords : Quality Assurance System, Achievement, and College.